Prevalence and associating factors of long COVID in pediatric patients during the Delta and the Omicron variants - Lokanuwatsatien, Tananya; Satdhabudha, Araya; Tangsathapornpong, Auchara; Bunjoungmanee, Pornumpa; Sinlapamongkolkul, Phakatip; Chaiyakulsil, Chanapai; Sritipsukho, Paskorn; Tantiyavarong, Pichaya (Frontiers in Pediatrics, 2023)
Introduction: The number of pediatric COVID-19 infections is increasing; however, the data on long COVID conditions in children is still limited. Our study aimed to find the prevalence of long COVID in children during the Delta and Omicron waves, as well as associated factors. Methods: A single-center prospective cohort study was conducted. We included 802 RT-PCR-confirmed COVID-19 pediatric patients in the Delta and Omicron periods. Long COVID was defined as symptoms lasting three months after infection. Parents and/or patients were interviewed by phone. To identify factors associated with long COVID, multivariable logistic regression was used. Results: The overall prevalence of long COVID was 30.2%. The Delta period had more prevalence than the Omicron (36.3% vs. 23.9%). Common symptoms for patients 0-3 years’ old were loss of appetite, rhinorrhea, and nasal congestion. Conversely, patients 3-18 years’ old had hair loss, dyspnea on exertion, rhinorrhea, and nasal congestion. Most symptoms improved after a 6-month follow-up. Factors associated with long COVID-19 conditions were infection during the Omicron period (adjusted OR 0.54; 95% CI 0.39-0.74, P < 0.001), fever (adjusted OR 1.51, 95% CI 1.03-2.23, P = 0.04) and rhinorrhea (adjusted OR 1.47, 95% CI 1.06-2.02, P = 0.02). Conclusion: Infection during the Omicron wave has a lower prevalence of long COVID. The prognosis is generally good, and symptoms become obscure over time. However, pediatricians may schedule appointments to monitor long COVID in children with fever or rhinorrhea as an initial symptom.